An Optimal FEC Based Solution to Head-of-Line Blocking - Mehrotra, Sanjeev (2014)
Head-of-Line (HOL) Blocking is a well known cause of performance degradation due to missing packets resulting in latency not only for themselves but also to dependent packets which have already arrived. Many existing approaches attempt to alleviate the issue by removing dependencies between packets so that packets which have already arrived have a lower chance of being delayed due to other packets which are missing. Other complimentary approaches use adhoc proactive retransmission or error correction to lower the probability of loss itself. In this paper, we show how application dependent requirements can be used in conjunction with network parameter estimates to provide an optimal approach to proactive retransmissions or error correction. In this approach, using network parameter estimates of bandwidth, delay, and loss, we first mathematically derive a probability distribution of the per packet delay which is then used to optimize parameters in a forward error correction framework given application requirements.